Psychosocial ergonomics of the workplace of medical staff during the COVID-19 pandemic in three risk’s dimensions: working hours, violence and the use of psychoactive drugs—a prospective pilot study - Rypicz, Łukasz; Gawłowski, Paweł; Witczak, Izabela; Humeńczuk-Skrzypek, Alicja; Salehi, Hugh Pierre; Kołcz, Anna (Frontiers in Public Health, 2023)
Workplace ergonomics should also be considered in the context of psychosocial factors 17 affecting the worker, which have a real impact on occupational risk. The present study examined 18 psychosocial risk factors in medical personnel in three domains: working hours, violence and 19 substance abuse. The purpose of the present study is to assess the current state of psychosocial 20 ergonomics of medical personnels by measuring occupational risks in the domains of: working 21 hours, violence and psychoactive substance abuse. The survey is consisted of two parts: socio-22 demographic information of participants and participants' assements of psychosocial risk factors. 23 In more than half of the respondents (52%), increased risk was identified in the domain of working 24 hours. Nearly half of the respondents (49.6%) have an identified high risk in the domain of violence, 25 and more than half of the respondents (52%) are at high risk in the domain of psychoactive substance 26 abuse.